Perancangan Aplikasi Mobile Pajak Daerah Di Kabupaten Ciamis - Uung Ungkawa; Marisa Premitasari; Muhammad Daffa Fathur Rahman; Rangga Alfyansyah; Dhiki Romadinur (Universitas Katolik Widya Karya Malang, 2023)
This research aims to design an Android-based local tax service information system at the Regional Financial Management Agency of Ciamis District. The system will facilitate access and processing of tax information through features such as online tax payment, tax registration, exemption request submission, and tax compliance reporting. The implementation of this system is expected to enhance the effectiveness and efficiency of tax services, as well as improve tax awareness and compliance in the community of Ciamis District.